Infant Gastroesophageal Reflux (GER): Benign Infant Acid Reflux or just Plain Aerophagia? - Kotlow, Lawrence (International Journal of Child Health and Nutrition, 2016)
Physicians are often asked to diagnose and treat infants with clinical signs of gastroesophageal reflux (GER) symptoms and in extreme cases gastroesophageal reflux disease (GERD). Some infants are left to work out their pain, regurgitation and vomiting until they outgrow the symptoms while others may undergo expensive, invasive endoscopic procedures in the operating room under general anesthesia. Initial treatment is often for infants to be placed on prescription adult acid reflux medications, which have limited benefits [1]. Drugs prescribed include: H-2 blockers such as ranitidine (Zantac), a proton pump inhibitor such as omeprazole (Prilosec) or lansoprazole (Prevacid). TOTS may cause aerophagia, a condition where the infant’s latch onto the mother’s breast or bottle allows the infant to swallow excessive amounts of air into the stomach during feeding. This aerophagia may be responsible for symptoms mimicking GER or GERD [2]. When these infants are examined for symptoms of GER the differential diagnosis of tethered oral tissues (TOTS) may not be addressed [3]. Tethered oral tissues may involve ankyloglossia (tongue-tied), maxillary and /or mandibular frenum lip-ties and in some instances buccal frenum ties. These tethered oral tissues (TOTS) prevent the infant from achieving a good seal onto the breast and or bottle with the resulting ingestion of excessive amounts of air. Background: When assessing infants presenting with gastroesophageal reflux symptoms, aerophagia secondary to tethered oral tissues (tongue-ties ,Lip-ties) should be considered in the differential diagnosis since the release of these tissues may eliminate the need for invasive gastrointestinal investigations and pharmacologic treatment of gastroesophageal reflux. Patient Pool: 340 infants ranging from 1 week to 3 months were referred for the evaluation and release of lingual and maxillary lips which were interfering with infant’s ability to achieve a good seal and latch onto the mother’s breast of infant bottle .The survey the parents completed indicated that 208 or 61% of the infants had signs of gastroesophageal reflux (GER) such as; vomiting, regurgitation, inability to sleep lying supine, fussiness, crying after nursing and morning congestion. Of the 208 infants 40% (83 infants) were or had been treated for GER with pharmacologic medications such as proton pump inhibitors or H2 blockers without any resolution of the symptoms. Findings: All of the infants presenting with these signs and symptoms underwent laser revisions of the tethered attachments. Upon completion of the procedure and at a 48 hour post-surgical follow-up discussion with the parents 93% (194 infants) of the infants showed immediate improvements and were able to breastfeed successfully without signs or symptoms of GER. Survey returned at the end of two weeks post-surgery had similar results Conclusion: Infants presenting with signs of GER should also be evaluated for restrictive tethered oral tissues (TOTS) such as ankyloglossia, lip and buccal ties. If they are present, strong consideration should be given to the release of these tissues as an initial approach. This may eliminate the need for pharmacologic treatment of GER.